Effect of ceramic particles on corrosion resistance of thermal sprayed stainless steel coating - TANG Quan (Journal of Materials Engineering, 2021)
The ceramic particles of different types and sizes reinforced stainless steel composite coatings were successfully prepared by high-velocity air fuel (HVAF) spraying technique. The effects of the types and sizes of ceramic particles on the hardness, porosity and corrosion resistance of the composite coating were systematically studied. The microstructure, hardness and corrosion behavior of stainless steel/ceramic particle composite coating were systematically characterized and analyzed by scanning electron microscope, automatic hardness tester, Image Pro Plus software and electrochemical workstation. The results show that the larger brown alumina (Al2O3) particles reinforced stainless steel composite coating has low porosity (0.7863%), high hardness (637HV0.1) and excellent corrosion resistance, and its self-corrosion potential is -454.14 mV and self-corrosion current density is 22.208 mA·cm-2. The fine silicon carbide (SiC) particles reinforced stainless steel composite coating also has a relatively high hardness (600HV0.1) and good corrosion resistance, and its self-corrosion potential is -463.68 mV and self-corrosion current density is 23.738 mA·cm-2.